OPTIMALISASI PERSALINAN NORMAL MELALUI “BIRTH PREPARATION CENTRE” DI KLINIK BERSALIN KOTA MEDAN TAHUN 2018 - Febrina Oktavinola Kaban; Farida Linda Sari Siregar; Evi Indriani br Karo (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2019)
Various programs attempt to reduce the maternal mortality rate implemented by the government to pregnant women. The activity